Pin Point Trachea: A Case Report - Ni Wayan Candrawati; Venny Singgih; Ketut Putu Yasa; Ida Bagus Ngurah Rai (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Pin point trachea is a rare case. It is caused by tuberculosis (TB) and trauma due to intubation procedure. Main complication of this abnormality is respiratory failure. It can be diagnosed through bronchoscopy. Managements of this abnormality are interventional bronchoscopy and treating the etiology. Surgery is considered if interventional bronchoscopy failed or cannot be performed.Case: A 29-year-old woman came to the emergency room complaining shortness of breath and hoarseness since two months before hospitalized. The patient also experienced cough, decreased body weight and appetite since 7 months earlier. The patient was diagnosed with bacteriologically confirmed TB and anti-TB drug was given. Cough symptom was decreasing but shortness of breath and hoarseness remained after treatment. Physical examination showed decreased vesicular sound and stridor. Bronchoscopy revealed narrow tracheal lumen (pin point) with fibrosis. Thoracic computed tomography (CT) scan showed severe narrowing of tracheal lumen at thoracic vertebrae 1-2. Surgery was performed to cut the fibrotic tissue and tracheostomy was placed at stenosis area.Conclusion: Pin point trachea is a rare case. One of the causes is tracheobronchial TB. The main managements are optimal administration of anti-TB drugs and interventional bronchoscopy or surgery.